Augmented Reality Comic-Based Learning: Its Impact on Student Learning Independence, Digital Literacy, and Literacy Achievement in Elementary Education - Zahratun Nufus; Saleman Mashood Warrah (LEOTECH: Journal of Learning Education and Technology, 2026)
The rapid advancement of digital technology in the Industry 4.0 era necessitates innovative instructional media capable of fostering independent learning, digital literacy, and literacy achievement among elementary school students. This study examines the effectiveness of Augmented Reality (AR)-based comic learning media in enhancing learning independence, digital literacy, and literacy achievement. A quantitative descriptive research design was employed, involving 78 fifth-grade students from two elementary schools in Cirebon City selected through total sampling. Data were collected using closed-ended questionnaires to measure learning independence and digital literacy, along with essay tests to assess literacy achievement. Instrument validity and reliability were evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM), while Multivariate Analysis of Variance (MANOVA) was applied to examine the simultaneous effects of school differences on the three dependent variables. The results indicate a significant multivariate effect of school context on the combined variables. Post hoc analysis reveals that school differences significantly influence literacy achievement, whereas differences in digital literacy and learning independence are not statistically significant. Correlation analysis demonstrates a strong association between digital literacy and learning independence, but no direct relationship with literacy achievement. These findings suggest that AR-based comics effectively enhance students’ literacy performance through immersive visualization and narrative engagement, while behavioral competencies such as learning independence and digital literacy require sustained implementation and pedagogical support. This study contributes an adaptable AR comic-based learning model suitable for elementary education, particularly in resource-limited schools, and provides empirical evidence of the integrated cognitive and behavioral impacts of immersive digital learning media.